Regional Autonomy Management from the Perspective of Human Resource Management - Purwanto; Rahmatulloh, Aang; Muliasutisna, Asep; Hanapia, Cepi; Pua Upa, Fatmawati (Jurnal Economic Resource, 2022)
Regional autonomy is a constitutional mandate that grants broad authority to regions to regulate and manage their own government affairs and local interests in accordance with laws and regulations. This policy not only serves as the foundation for good governance, but also as a strategy for empowering regions in facing the demands of globalisation. This study aims to analyse regional autonomy management from a human resource management (HRM) perspective, focusing on the role of regional leaders and the competence of civil servants (ASN) in supporting the effectiveness of regional governance. The research design is descriptive qualitative with a case study approach. The research population includes all government officials in the New Autonomous Regions (DOB) that are the research locations, while the sample was selected purposively based on their direct involvement in the planning, implementation, and evaluation of regional policies. Data were collected through in-depth interviews, observations, and document reviews, then analysed using thematic analysis to identify patterns and relationships between variables. The results of the study indicate that the success of regional autonomy management is greatly influenced by visionary leadership, professional civil servant competence, and an organisational culture oriented towards public service. Effective human resource management implementation can strengthen institutional capacity, improve service quality, and promote regional autonomy. These findings imply the need for strengthening capacity building of civil servants, implementing a merit-based system in recruitment and promotion, and conducting consistent performance evaluations to ensure the sustainability of regional autonomy.